Exploring aptamers for targeted enrichment of X sperm in bovine: unraveling selective potential - Sumit Kumar Singh; Rohit Kumar; Manya Mathur; Himanshu Kamboj; Jai Kumar Kaushik; Ashok Kumar Mohanty; Sudarshan Kumar (Animal Biotechnology, 2024)
Nucleic acid aptamers have been used in the past for the development of diagnostic methods against a number of targets such as bacteria, pesticides, cancer cells etc. In the present study, six rounds of Cell-SELEX were performed on a ssDNA aptamer library against X-enriched sperm cells from Sahiwal breed cattle. Sequencing was used to examine the aptamer sequences that shown affinity for sperm carrying the X chromosome in order to find any possible X-sperm-specific sequences. Out of 35 identified sequences, 14 were selected based on bioinformatics analysis like G-Score and Mfold structures. Further validation of their specificity was done via fluorescence microscopy. The interaction of biotinylated-aptamer with sperm was also determined by visualizing the binding of streptavidin coated magnetic beads on the head region of the sperm under bright field microscopy. Finally, a real-time experiment was designed for the validation of X-sperm enrichment by synthesized aptamer sequences. Among the studied sequences, aptamer 29a exhibited a higher affinity for X sperm compared to Y sperm in a mixed population of sperm cells. By using aptamer sequence 29a, we obtained an enrichment of 70% for X chromosome bearing sperm cells.